DIGITAL DILEMMA: INVESTIGATING PARENTS’ CONCERNS ABOUT PRESCHOOL TECHNOLOGY ADDICTION - Kabadayi, Abdülkadir (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
In the digital age, technology use among young children has rapidly increased, raising significant concerns among parents about its potential impact on early development. This qualitative study explores parents’ perceptions, anxieties, and coping strategies regarding technology addiction in preschool-aged children. Through semi-structured interviews with parents of children aged 3 to 6, the study identifies key themes such as fears of delayed social, emotional, and cognitive development, struggles with setting screen time boundaries, and the perceived conflict between technology’s educational benefits and its addictive risks. It is a qualitative study and 10 parents participated the research. Findings highlight that while parents acknowledge the value of technology for learning, they also express concerns about excessive use, the impact on social skills, and the difficulty of maintaining a balanced rutine. Findings reveal that while parents acknowledge the role of digital tools in modern education, they express deep concerns over behavioral dependency, decreased physical activity, and impaired family interactions. The study highlights the need for increased parental guidance resources, balanced technology integration strategies, and support mechanisms within early childhood education frameworks to foster healthier digital habits. These insights contribute to understanding how families navigate the digital dilemma in the formative preschool years and underscore the importance of sustainable technology use for holistic child development.